2010
DOI: 10.1089/aid.2010.0059
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir Outcomes Study: Comparative Effectiveness of Virologic Suppression, Regimen Durability, and Discontinuation Reasons for Three-Class Experienced Patients at 48 Weeks

Abstract: Several new antiretroviral (ARV) agents for treatment experienced HIV-infected patients have been approved since June 2006, including darunavir (DRV) and raltegravir (RAL). While efficacious in clinical trials, the effectiveness, durability, and tolerability of these new ARVs remains understudied in the context of routine clinical care. The Darunavir Outcomes Study is a prospective cohort study of three-class ARV-experienced patients changing regimens at the 1917 Clinic after 1/7/2006. All treatment decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
(44 reference statements)
2
28
0
Order By: Relevance
“…On October 12, 2007 the Food and Drug Administration (FDA) approved raltegravir—the first HIV integrase inhibitor—for use in treatment-experienced persons with HIV. Raltegravir has improved outcomes for persons with HIV infection resistant to previously available therapies [5, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…On October 12, 2007 the Food and Drug Administration (FDA) approved raltegravir—the first HIV integrase inhibitor—for use in treatment-experienced persons with HIV. Raltegravir has improved outcomes for persons with HIV infection resistant to previously available therapies [5, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, information about these long-term real-life outcomes is sparse in patients receiving ATV/r [11][12][13] and in patients receiving boosted PI-based therapy in general, 15 especially in the case of treatment-experienced patients. 16,17 Therefore, the aim of the current study was to evaluate the long-term outcomes of ATV/r-based regimens in a large sample of ARV-experienced patients in a real-life European clinical setting. To our knowledge this represents the largest cohort to date evaluating long-term outcomes of a boosted PI-based regimen in ARV-experienced patients.…”
mentioning
confidence: 99%
“…However, the backbone components of these PI-based regimens were not taken into account for this analysis. Reviewing these studies individually, none separately evaluated the different NRTI backbones, and several excluded use of abacavir altogether [810, 1522]. …”
Section: Discussionmentioning
confidence: 99%
“…Darunavir also offers superior potency and better short- and long-term tolerability, making its use more clinically practical than many first-generation PIs. Clinical trial data have indicated that treatment-experienced patients receiving DRV/r are more likely to reach and maintain treatment response when compared with antiretroviral-experienced patients receiving other ritonavir-boosted PIs [810]. …”
Section: Introductionmentioning
confidence: 99%